Analysis of the structural behavior of an innovative reinforced ski boot - Petrone, N.; Marcolin, G.; Centofante, E.; Atzori, B. (Procedia Engineering, 2010)
The effect on the boot structural behavior of a stiffening aluminum bootboard has been investigated by laboratory and field tests. Stiffness tests on the boot with the bootboard screwed to the shell (state ON) showed a 20% increase with respect to the unscrewed state (OFF). Lateral stiffness tests conducted on a servohydraulic test bench together with motion capture techniques did not show significant increases due to the bootboard. Strain gauges applied to the bootboard for measuring torsion and bending moments in the field confirmed the intervention of the bootboard torsional stiffness at the edge changes during slalom turns.